1951
DOI: 10.1084/jem.93.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Inherited Traits of H. Influenzae by Desoxyribonucleic Acid Fractions Isolated From Type-Specific Cells

Abstract: Change of non-typable (R) strains of H. influenzae into the specific type of origin or new types (S) has been effected in vitro in a predictable fashion within a single 24 hour growth period, by a desoxyribonucleic acid-containing fraction isolated from type-specific cells of the type desired. Only a small proportion of the population of R cells are susceptible to the change induced in inherited characteristics by the desoxyribonucleic acid fraction. The data suggest that the number of susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

1953
1953
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(57 citation statements)
references
References 8 publications
0
57
0
Order By: Relevance
“…NTHi strain 86-028NP is a minimally passaged clinical isolate from a patient who underwent tympanostomy and tube insertion for chronic OM (Suzuki & Bakaletz, 1994). H. influenzae strain Rd KW20 was originally isolated over 60 years ago (Alexander & Leidy, 1951) and its genome was sequenced in 1995 (Fleischmann et al, 1995). Isolates of H. influenzae were routinely maintained on chocolate agar with bacitracin at 37 uC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NTHi strain 86-028NP is a minimally passaged clinical isolate from a patient who underwent tympanostomy and tube insertion for chronic OM (Suzuki & Bakaletz, 1994). H. influenzae strain Rd KW20 was originally isolated over 60 years ago (Alexander & Leidy, 1951) and its genome was sequenced in 1995 (Fleischmann et al, 1995). Isolates of H. influenzae were routinely maintained on chocolate agar with bacitracin at 37 uC.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to haem utilization, the Rd tehB mutant was marginally impaired in haem utilization and thus the effect of complementation was difficult to discern. This difference likely reflects the genetic differences between the pathogenic, clinically isolated, type b isolate 10810 and the multiply passaged Rd KW20 isolate, which was originally isolated over 60 years ago (Alexander & Leidy, 1951).…”
Section: Role Of Tehb In Resistance To Tellurite and Oxidationmentioning
confidence: 99%
“…Following internalization, the DNA can be inserted into the chromosome by homologous recombination. While Hi isolates are competent and can be readily transformed in the laboratory environment (Alexander & Leidy, 1951), the contribution of homologous recombination to population structure in nature is less clear. One phylogenetic study (Feil et al, 2001) found relatively high congruence between housekeeping loci, suggesting that homologous recombination was not frequent enough to scramble phylogenetic signals.…”
Section: Introductionmentioning
confidence: 99%
“…From the genetic point of view the most typical aspect of recombination in this strain is that exchange of some genetically determined characters involves, a t the same time, the exchange of other physiologically unrelated characters with a high probability. Moreover, whole cells have so far been found necessary for recombination to occur, in contrast with transformations or genetic transfers in other bacterial species, such as pneumococcus (Avery, MacLeod & McCarty, 1944 ;Griffith, 1928 ;Hotchkiss, 1951), HaemophiZus (Alexander & Leidy, 1951 ) and Salmonella typhimuriuin (Zinder & Lederberg, 1952), which have been demonstrated by means of cell-free preparations. Thus, transfer of genetic material in Bact.…”
mentioning
confidence: 99%